Elevated serum matrix metalloprotease (MMP-2) as a candidate biomarker for stable COPD - Mahor, Durga; Kumari, Vandana; Vashisht, Kapil; Galgalekar, Ruma; Samarth, Ravindra M.; Mishra, Pradyumna K.; Banerjee, Nalok; Dixit, Rajnikant; Saluja, Rohit; De, Sajal; Pandey, Kailash C. (BMC pulmonary medicine, 2020)
The increasing trend of Chronic Obstructive Pulmonary Disease (COPD) in becoming the third leading cause of deaths by 2020 is of great concern, globally as well as in India. Dysregulation of protease/anti-protease balance in COPD has been reported to cause tissue destruction, inflammation and airway remodelling; which are peculiar characteristics of COPD. Therefore, it is imperative to explore various serum proteases involved in COPD pathogenesis, as candidate biomarkers. COPD and Asthma often have overlapping symptoms and therefore involvement of certain proteases in their pathogenesis would render accurate diagnosis of COPD to be difficult. Serum samples from controls, COPD and Asthma patients were collected after requisite institutional ethics committee approvals. The preliminary analysis qualitatively and quantitatively analyzed various serum proteases by ELISA and mass spectrometry techniques. In order to identify a distinct biomarker of COPD, serum neutrophil elastase (NE) and matrix metalloprotease-2 (MMP-2) from COPD and Asthma patients were compared; as these proteases tend to have overlapping activities in both the diseases. A quantitative analysis of the reactive oxygen species (ROS) in the serum of controls and COPD patients was also performed. Statistical analysis for estimation of p-values was performed using unpaired t-test with 95% confidence interval. Amongst the significantly elevated proteases in COPD patients vs the controls- neutrophil elastase (NE) [P < 0.0241], caspase-7 [P < 0.0001] and matrix metalloprotease-2 (MMP-2) [P < 0.0001] were observed, along with increased levels of reactive oxygen species (ROS) [P < 0.0001]. The serum dipeptidyl peptidase-IV (DPP-IV) [P < 0.0010) concentration was found to be decreased in COPD patients as compared to controls. Interestingly, a distinct elevation of MMP-2 was observed only in COPD patients, but not in Asthma, as compared to controls. Mass spectrometry analysis further identified significant alterations (fold-change) in various proteases (carboxy peptidase, MMP-2 and human leukocyte elastase), anti-proteases (Preg. zone protein, α-2 macroglobulin, peptidase inhibitor) and signalling mediators (cytokine suppressor- SOCS-3). The preliminary study of various serum proteases in stable COPD patients distinctly identified elevated MMP-2 as a candidate biomarker for COPD, subject to its validation in large cohort studies.